(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Bioremediation is a process of using naturally occurring species to break down hazardous substances into less harmful or non-toxic substances. Effluents from petroleum refinery pose a serious health hazard on the people who depend on the water as source of supply for domestic uses. To avoid health hazard, it is imperative for these toxic compounds to be removed from waste water before its disposal. The primary goal of this study was to carry out bioremediation of petroleum refinery effluents using mutant strains of fungal consortia. Refinery effluents were collected under the storage tank in Kaduna Refining and Petrochemical Company, Kaduna, Nigeria. Effluent samples were analyzed for total petroleum hydrocarbons using Gas Chromatography and Mass Spectroscopy (GC-MS). Standardization of the fungal consortium inoculum was prepared following standard method. The culture medium of each isolate of the mutated fungi Aspergillus niger, A. fumigatus, A. versicolor and A. quadrilineatus was carried out following standard procedure. The result of the GC-MS analysis revealed that cis-13-Octadecenoic acid, methyl ester; 7-Hexadecenoic acid, methyl ester; 10-Octadecenoic acid, and Methyl stearate; showed the highest percentage quality of (99%) respectively. Bioremediation of Kaduna refinery effluents in this study indicated that, there was decline in the bioremediation parameters in the second week up to the fourth week whereby the COD, BOD all showed significant decrease. Based on the Gas Chromatographic (GC) analysis of the fungi consortium, the degradative ability of the mutants of Aspergillus versicolor and Aspergillus quadrilineatus were observed to be prominent.